EVALUATION OF QUALITY OF LIFE IN PATIENTS WITH SCOLIOSIS SUBMITTED TO CONSERVATIVE TREATMENT - MONTENEGRO,EMILLY GALVÍNCIO (2020)
ABSTRACT Objective To assess the level of quality of life (QOL) and the most affected dimensions in patients with scoliosis. Methods Original article about a descriptive, quantitative study of 20 individuals diagnosed with scoliosis and undergoing conservative treatment. Data were collected during consultations using two questionnaires, one containing social and demographic data and the Revised Scoliosis Research Society-22 (Brazilian version). The analysis was carried out in the Statistical Package for the Social Sciences (version 25), using descriptive statistics and the nonparametric Mann-Whitney test. The research was submitted to and approved by the Institutional Review Board of the Faculdades Integradas de Patos. Results The sample was composed mostly of female patients (70%), aged between 12 and 16 years (55%), whose most affected QOL domains were activity (10%) and mental health(55%). In addition, patients with moderate scoliosis had a lower quality of life when compared to those with mild scoliosis. Conclusion Scoliosis is an alteration of the spine that affects more female adolescents, negatively impacting their quality of life, and mainly affecting the domains of activity, mental health and appearance. Given this reality, a closer look is needed, seeking to create and encourage strategies that can improve the overall well-being of these patients. Level of Evidence II - Retrospective Study.